The ethical image in a topological perspective: the poetics of Gaston Bachelard (Altre Modernità, 2012)
In the poetics of Gaston Bachelard, the natural images, especially the four elements (fire, water, air, earth), occupy the eminent place for literary imagination. Under this main frame, this paper tries to present the relation of ethics and aesthetics in focusing on the ethical image as a synthetic concept. It also argues that the poetic imagination in Bachelard presupposes a metaphysical base managing the being, the force, the will, and the action. There is a dynamic structure in this metaphysics of imagination. Notwithstanding the usual separation of different spheres in philosophy, Bachelard urges a primary fusion in the cosmic scale, i.e. the world and the human are communicative and correspondent. Taking these principles into consideration, this paper explores the topological dimension in those poetic images of elements and space. The ontological sense of being-there is evaluated by the dynamic function of “there” in restoring its ethical meaning. Likewise, the terms “in front of the fire”, “before the water”, “in the water” are given the topological accents. The verticality indicating the dynamic function of the flight, of the falling, and of standing upright is topologically effective. In accordance to the verticality, the concept of survival contains an effect of surpassing the existential conditions, the prefix “sur-“ means that tentative of the higher degree. In sum, the cosmicity as the very place of ethical and ontological unification reveals Bachelard’s concern on the imaginative transformation of the personality, the appropriation in the cosmos.